Study on physical properties of Acacia mangium and Acacia auriculiformis of plantation growth and natural regeneration - Bawon, Paiman; Abu Samah, Mohd Armi (2015)
This study was carried out to evaluate the pysical properties of stressed and non-stressed of matured and plantation grown Acacia hybrid. The mean of the specific gravity of timber from stressed and non-stressed of matured natural regenerated stand was 0.67 and 0.61 respectively.